A phase field – Finite element approach to model the interaction between phase transformations and plasticity in shape memory alloys. (May 2016) - Paranjape, Harshad M.; Manchiraju, Sivom; Anderson, Peter M.
Abstract: The coupling between phase transformations and plasticity in shape memory alloys (SMAs) is studied by developing a finite element framework in which the constitutive relation captures both phase transformations at the martensite correspondence variant (CV) scale and rate-dependent crystal plasticity in austenite. Load-free and load-biased thermal cycling simulations involving a model cubic-to-tetragonal transformation system are carried out to study how slip in austenite can affect the resulting martensite microstructure. Three key questions are answered. First, where does austenite slip predominantly occur during phase transformation? Second, at what stage during a thermal cycle is plastic deformation most pronounced? Third, what is the effect of plastic deformation on measurable parameters like transformation temperature and subsequent transformation microstructure? The model can also be generalized to study the coupling between phase transformations, twining, and slip. Highlights: We develop a new micromechanical model coupling phase transformation and austenite plasticity in Shape Memory Alloys (SMA). We model martensite correspondence variant scale phase transformation and reorientation using the phase field method. We model slip in the austenite phase using a crystal plasticity based framework with a phenomenological hardening rule. We systematically study the spatial and temporal trends in the interaction between phase transformation and austenite slip. The model has broader impacts, in that the framework can include other inelastic mechanisms, such as twinning.